Monitoring Persona: Mediatized Identity and the Edited Public Self - Marshall, P. David (FRAME, Journal of Literary Studies, 2026)
One of the key transformations in contemporary culture is the insistent demand to construct a public persona. Constructing a persona for navigating through life is not new; what is new is the naturalization of producing a mediatized version of this public self. The complexity of producing an online public identity involves the labour of monitoring and editing ourselves, connecting with strategic purpose to others and building recognizable reputations. This article both identifies and concludes that what we are experiencing is the work and relative value of producing a mediatized identity — a persona — which is a form of identity often linked to celebrities in our traditional media industries and now pandemic in contemporary culture.